Potential of The Biological Agent Bacillus spp in Inhibiting Fusarium Wild Disease and its Effects on The Growth and Production of Cayenne Papper (Capsicum frutescens L.) - Zakqy, Nauval; Wuryandari, Yenny; Purnawati, Arika (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Cayenne pepper (Capsicum frutescens L.) is a horticultural crop in Indonesia that often has many obstacles. The main obstacle that is often faced is wilt disease caused by the fungus Fusarium oxysporum. Bacillus spp. bacteria have the potential to control the fungus F. oxysporum. The purpose of this study was to determine the ability of Bacillus spp. bacteria in controlling fusarium wilt disease. This research was conducted from August to November 2023 at the Plant Health Laboratory and screen house of the Faculty of Agriculture, National Development University "Veteran" East Java. The study used a Factorial Complete Randomized Block Design with three replications and nine treatments so that there were 27 experimental units. The observation variables included incubation period, disease intensity, plant height, number of leaves, first flower appearance and fruit wet weight. The research data were analyzed using ANOVA analysis of variance procedure to determine whether there is an effect of each treatment. If it is known that there is a significantly different effect from the treatment, it will be continued with the DMRT test at the 5% level. The results showed that the combination of Bacillus spp bacteria and dosage had an effect on the incubation period and disease intensity. The results showed that the combination of Bacillus spp bacteria and doses had an effect on vegetative phase parameters, namely plant height and number of leaves. However, the combination of Bacillus spp and dosage showed that the generative phase parameters did not significantly affect the first flower appearance and fruit wet weight